2018
DOI: 10.1111/age.12725
|View full text |Cite
|
Sign up to set email alerts
|

Early adipose deposits in sheep: comparative analysis of the perirenal fat transcriptome of Assaf and Churra suckling lambs

Abstract: Adipose deposits influence the quality of ruminant carcasses, and in suckling lambs, internal types of adipose deposits represent a notable proportion of total fat. The aim of this study was to perform a comparative analysis of the perirenal fat transcriptomes of suckling lambs from two breeds with different growth and carcass characteristics. The perirenal fat tissue from 14 suckling lambs (Assaf, n = 8; Churra, n = 6) was used for the RNA-seq analysis. The functional enrichment analysis of the 670 highly exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
(86 reference statements)
1
13
0
Order By: Relevance
“…The majority of adipose transcriptome studies using high-throughput RNA sequencing (RNA-Seq) have been limited to mice [20,21], sheep [22][23][24], pigs [25][26][27], and humans [28][29][30]. Adipose transcriptomes are affected by the type of adipose, as well as by the sex and age of the animal [31].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of adipose transcriptome studies using high-throughput RNA sequencing (RNA-Seq) have been limited to mice [20,21], sheep [22][23][24], pigs [25][26][27], and humans [28][29][30]. Adipose transcriptomes are affected by the type of adipose, as well as by the sex and age of the animal [31].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, results from an RNAseq study on perirenal BAT of six-month-old lambs subjected to cold conditions for 25 days reported an expression of UCP1 [ 65 ]. Another study using the same tissue from suckling lambs reported an expression of UCP1 through RNAseq at 19−35 days of age [ 66 ]. Yuan et al [ 67 ] reported different levels of expression of this gene from 2 to 12 months of age, where lower levels were found in superficial fat, and higher levels were seen in deep fat deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Coexpression networks of the differentially expressed genes indicated TCONS_00372767, TCONS_00171926, TCONS_00054953, and TCONS_00373007 might play important roles in tail fat deposition (Ma et al, 2018). In addition, by using RNA-seq, perirenal fat transcriptomes of Assaf and Churra suckling lambs with different early-life fattening patterns were analyzed (Suárez-Vega et al, 2018). It was shown that 23 lncRNAs were robustly expressed in all samples.…”
Section: Sheepmentioning
confidence: 99%
“…It was shown that 23 lncRNAs were robustly expressed in all samples. Among them, ENSOARG00000025723 and ENSOARG00000026925 were shown positionally linked to genes related to fat and adipose tissue, which might play a role in early adipose deposits in sheep (Suárez-Vega et al, 2018). Overall, studies on the lncRNAs in farm animals are just starting and a surge of literature in lncRNAs in adipogenic regulation of farm animals is expected in the following years.…”
Section: Sheepmentioning
confidence: 99%